De-familiarising Nationalist Discourses: Performative Ironies of the Normative Indian Episteme - Das, Indian Institute of Technology, Kharagpur, India, Saswat S.; Purakayastha, Kazi Nazul University, India, Anindya Sekhar; Sarkar, Vellore Institute of Technology, India, Sandeep (Asiatic: IIUM Journal of English Language and Literature, 2014)
The present excursus attempts a deconstructive reading of the foundational texts of normative Indian nationalism and problematises them and their epistemic plexus through the critical trajectories of Homi K. Bhabha and Partha Chatterjee. Nationalism still remains a primary signifier in academic debates and in works like The Nation and its Fragments and Nationalist Thoughts and the Colonial World, Chatterjee challenges the assumption that nationalism in Asia and Africa is a derivative version of pre-given European nationalist a prioris. For Chatterjee, Asian and African nationalism was based on difference and not on derivation and the present essay addresses this differentiality, this dynamics of performative operativity of Indian nationalism with specific references to textual episteme of foundational thinkers such as Tagore, Gandhi, Vivekananda and Jawaharlal Nehru. We interrogate the normative cognitivities of these foundational thinkers by pitting them against the radical conceptualisation of DissemiNation of Homi K. Bhabha. We argue that while the foundational texts of Indian nationalism did not imitate the epistemic structures of the West they ended up in offering only mythic abstractions and religious normativities that surely fail to betray any proud deliberative encounter with â€œthe historic and objective realitiesâ€ of India.